2017
DOI: 10.1108/jica-06-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ views on integrated care

Abstract: Purpose Integrated care policies have been at the heart of recent health reforms in many European countries. The purpose of this paper is to study the integration from the perspective of health care personnel working in primary health care clinics. Design/methodology/approach The study employs data from interviews collected in a research project examining patient choice and integrated care in primary health care clinics in Finland. The interviews were conducted in five cities in Southern Finland in 17 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Information sharing, trust and acknowledging the skills and capabilities of sectors were mutual findings. The importance of information exchange and communication further concurs with the study by Jolanki et al (2017). This was particularly the case about knowledge and access to third sector servicesrespondents simply highlighted that they did not know how or where to access information, and that clarity and communication of offerings were simply required.…”
Section: Discussionsupporting
confidence: 71%
“…Information sharing, trust and acknowledging the skills and capabilities of sectors were mutual findings. The importance of information exchange and communication further concurs with the study by Jolanki et al (2017). This was particularly the case about knowledge and access to third sector servicesrespondents simply highlighted that they did not know how or where to access information, and that clarity and communication of offerings were simply required.…”
Section: Discussionsupporting
confidence: 71%
“…Digital competence comprises not only IT skills but also the ability to meet complex demands using psychosocial resources (including skills and attitudes) in a particular circumstance [5]. For patients with multiple care needs, nurses should tailor care between social care and healthcare [42, 43]. In these situations, a fluent exchange of information between professionals and organizations is important for care continuity.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Therefore, it is important to identify novel competences required to overcome present inadequacies, such as poor communication, "silo" thinking and unclear responsibilities, that hinder care integration. 1 For example, Jolanki et al 1 found that patients in health care clinics were forced to take an active role as the coordinator of their care, which is in contradiction with the idea of peoplecentered care. 7 In line with previous scarce research, a recent report 12 emphasizes generic competences learned and shared by all professional groups as a prerequisite for successful reform.…”
Section: Introductionmentioning
confidence: 99%